Graft Copolymer Resin
A graft copolymer resin with a specific degree of swelling in a mixed solvent improves solvent resistance and impact resistance in rubber-reinforced thermoplastic resins, addressing the need for enhanced chemical resistance in industrial and home appliance applications.
Patent Information
- Application Number
- JP2020211447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Rubber-reinforced thermoplastic resins require improved chemical resistance, particularly solvent resistance, to enhance the quality of industrial and home appliance products.
A graft copolymer resin is produced by graft polymerizing a vinyl monomer containing an aromatic vinyl monomer onto a rubber-like polymer with a structural unit derived from a (meth)acrylic acid ester, ensuring a degree of swelling of 8.0 or more in a mixed solvent of methyl ethyl ketone and toluene.
The resulting resin exhibits enhanced solvent resistance, weather resistance, and impact resistance, while maintaining fluidity.
Smart Images

Figure 0007601630000001 
Figure 0007601630000002 
Figure 0007601630000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a graft copolymer resin. [Background technology]
[0002] Rubber-reinforced thermoplastic resins are excellent in moldability, impact resistance, mechanical strength, etc., and are widely used in industrial parts and household electrical appliances. In these applications, they often come into contact with various chemicals, detergents, etc., and so it is necessary to impart chemical resistance to the rubber-reinforced thermoplastic resins.
[0003] For example, Patent Documents 1 to 3 describe that rubber-reinforced thermoplastic resins obtained by graft-polymerizing a specific monomer onto an acrylic rubber-like polymer have excellent chemical resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-173361 [Patent Document 2] Japanese Patent Application Publication No. 8-113689 [Patent Document 3] Japanese Patent Application Publication No. 9-316291 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for rubber-reinforced thermoplastic resins with improved chemical resistance in order to improve product quality, etc. Therefore, an object of the present invention is to provide a rubber-reinforced thermoplastic resin with improved chemical resistance, particularly improved solvent resistance. [Means for solving the problem]
[0006] As a result of intensive research conducted by the present inventors in order to solve the above problems, it has been found that the above problems can be solved by the invention described in [1] below. [1] A graft copolymer resin obtained by graft polymerizing a vinyl monomer including an aromatic vinyl monomer onto a rubber-like polymer including a structural unit derived from a (meth)acrylic acid ester, A graft copolymer resin, wherein the graft copolymer contained in the graft copolymer resin has a swelling degree of 8.0 or more in a mixed solvent of methyl ethyl ketone and toluene (mass ratio 1:1). Effect of the Invention
[0007] According to the present invention, it is possible to provide a rubber-reinforced thermoplastic resin having improved solvent resistance. Furthermore, the rubber-reinforced thermoplastic resin of the present invention has sufficient weather resistance, impact resistance and flowability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Preferred embodiments of the present invention will now be described.
[0009] The graft copolymer resin of the present embodiment is obtained by graft polymerizing a vinyl monomer including an aromatic vinyl monomer onto a rubber-like polymer including a structural unit derived from a (meth)acrylic acid ester. The graft copolymer resin includes a graft copolymer in which a vinyl monomer is graft polymerized onto a rubber-like polymer, a free resin in which vinyl monomers are polymerized together, and may include unreacted vinyl monomers, etc.
[0010] Examples of the rubbery polymer include (meth)acrylic rubbery polymers mainly composed of (meth)acrylic acid ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; composite rubbery polymers of butadiene rubbery polymer / (meth)acrylic rubbery polymer; composite rubbery polymers of silicone rubbery polymer / (meth)acrylic rubbery polymer, etc. These may be used alone or in combination of two or more.
[0011] Among these rubbery polymers, from the viewpoint of further improving the solvent resistance, a (meth)acrylic rubbery polymer is preferred, a (meth)acrylic rubbery polymer containing a structural unit derived from an alkyl ester of (meth)acrylic acid is more preferred, and a (meth)acrylic rubbery polymer containing a structural unit derived from an alkyl ester of (meth)acrylic acid having 4 or more carbon atoms in the alkyl group is even more preferred. The content of the structural unit derived from an alkyl ester of (meth)acrylic acid (particularly an alkyl ester of (meth)acrylic acid having 4 or more carbon atoms in the alkyl group) in the (meth)acrylic rubbery polymer is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, from the viewpoint of further improving the solvent resistance. The upper limit of the content of the structural unit derived from an alkyl ester of (meth)acrylic acid in the (meth)acrylic rubbery polymer is not particularly limited, but can be, for example, 95% by mass or less.
[0012] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate.
[0013] The rubber-like polymer may be crosslinked with a crosslinking agent, such as divinylbenzene, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, diallyl phthalate, dicyclopentadiene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triallyl cyanurate, and triallyl isocyanurate.
[0014] The rubber-like polymer may have a structural unit derived from a monomer other than the above-mentioned (meth)acrylic acid alkyl ester, such as a structural unit derived from a conjugated diene monomer, an aromatic vinyl monomer, or a vinyl cyanide monomer.
[0015] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2-chloro-1,3-butadiene, chloroprene, 2-methyl-1,3-butadiene, and 2,3-dimethyl-1,3-butadiene, and these can be used alone or in combination.
[0016] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, paramethylstyrene, bromostyrene, etc., and one or more of these can be used.
[0017] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, ethacrylonitrile, fumaronitrile, etc., and one or more of these can be used.
[0018] The content of the structural units derived from the conjugated diene monomer, aromatic vinyl monomer or vinyl cyanide monomer in the rubbery polymer can be, for example, 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. When the rubbery polymer contains these structural units, the lower limit of the content is not particularly limited, but each can be, for example, 1% by mass or more.
[0019] The rubber-like polymer can be produced by a conventional method, for example, emulsion polymerization, which may be carried out in the presence of a polymerization initiator, an emulsifier, a polymerization regulator, etc.
[0020] Examples of the polymerization initiator include water-soluble polymerization initiators such as potassium persulfate, sodium persulfate, and ammonium persulfate, and oil-soluble polymerization initiators such as cumene hydroperoxide, benzoyl peroxide, t-butyl hydroperoxide, acetyl peroxide, diisopropylbenzene hydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide.
[0021] Examples of the emulsifier include carboxylates, sulfates, sulfonates, etc. Specific examples of emulsifiers that are preferably used include potassium oleate, dipotassium alkenyl succinate, sodium rosinate, potassium rosinate, disproportionated sodium rosinate, potassium disproportionated rosinate, sodium dodecylbenzenesulfonate, etc.
[0022] Examples of the polymerization regulator include alkyl mercaptans such as n-dodecyl mercaptan and t-dodecyl mercaptan.
[0023] From the viewpoint of improving the impact resistance of the graft copolymer resin, the above rubber-like polymer preferably has a gel content of 75 to 96%. The gel content of the rubber-like polymer is measured, for example, by the method described later in the Examples.
[0024] From the viewpoint of the balance between impact resistance and fluidity, the graft copolymer resin preferably contains the rubber polymer in an amount of 10 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 40 to 70 mass %.
[0025] The vinyl monomer used in the graft polymerization includes an aromatic vinyl monomer. The vinyl monomer preferably further includes a vinyl cyanide monomer and / or an alkyl (meth)acrylate ester. The aromatic vinyl monomer, the vinyl cyanide monomer, and the alkyl (meth)acrylate ester may be the same as those described above.
[0026] The content of the aromatic vinyl monomer used in the graft polymerization can be, for example, 50 to 90 mass%, preferably 55 to 85 mass%, more preferably 60 to 80 mass%, based on the total amount of vinyl monomers. The content of the vinyl cyanide monomer used in the graft polymerization can be, for example, 10 to 40 mass%, preferably 15 to 35 mass%, more preferably 20 to 30 mass%, based on the total amount of vinyl monomers.
[0027] The content of the (meth)acrylic acid alkyl ester in the vinyl monomer used in the graft polymerization is preferably 5 to 30 mass % based on the total amount of the vinyl monomer, from the viewpoint of further improving the solvent resistance.
[0028] The graft copolymer resin can be produced by a conventionally known method, and examples of the polymerization methods that can be used include emulsion polymerization, suspension polymerization, and bulk polymerization. When emulsion polymerization is used, the rubber-like polymer is graft-polymerized with the vinyl monomer to obtain a latex of the graft copolymer resin. The latex of the graft copolymer resin is solidified by a known method, and is washed, dehydrated, and dried to obtain a powder of the graft copolymer resin.
[0029] The swelling degree of the graft copolymer contained in the graft copolymer resin of this embodiment in a mixed solvent of methyl ethyl ketone and toluene (mass ratio 1:1) is 8.0 or more, preferably 9.0 or more, and more preferably 10.0 or more. By satisfying this requirement, the solvent resistance of the graft copolymer resin is improved. The upper limit of the swelling degree is not particularly limited, but can be, for example, 25.0 or less.
[0030] The swelling degree of the graft copolymer in the graft copolymer resin can be adjusted to the above-mentioned predetermined range, for example, by adopting some or all of the following methods. (A) t-Dodecyl mercaptan is added during the production of the rubbery polymer. (B) In the vinyl monomer used in the graft polymerization, the content of the (meth)acrylic acid alkyl ester having an alkyl group with 4 or more carbon atoms is adjusted to, for example, 10 to 30 mass %. (C) As an emulsifier used in the production of the rubber-like polymer, for example, rosin acid or a derivative thereof is used.
[0031] In this specification, the graft copolymer refers to a graft copolymer resin that is added with acetone, and then the insoluble portion is separated from the soluble portion by centrifugation or the like, and the insoluble portion is separated. The swelling degree of the graft copolymer in a mixed solvent of methyl ethyl ketone and toluene (mass ratio 1:1) can be determined by dividing the weight of the graft copolymer after the graft copolymer is fully swollen in a mixed solvent of methyl ethyl ketone and toluene (mass ratio 1:1) by the weight of the graft copolymer after the mixed solvent is removed by drying. Specifically, the graft copolymer can be separated from the graft copolymer resin by the method described in the Examples, and the swelling degree of the separated graft copolymer can be determined.
[0032] The graft copolymer resin of the present embodiment can be mixed with various thermoplastic resins to form a thermoplastic resin composition. Examples of the thermoplastic resin include polystyrene, styrene-acrylonitrile copolymer, styrene-methyl methacrylate copolymer, polymethyl methacrylate, styrene-maleic anhydride copolymer, styrene-maleimide copolymer, rubber-reinforced polystyrene (HIPS), acrylonitrile-butadiene-styrene resin (ABS resin), acrylonitrile-ethylene propylene-styrene resin (AES resin), methyl methacrylate-butadiene-styrene resin (MBS resin), acrylonitrile-n-butyl acrylate-styrene resin (AAS resin), polycarbonate, polyamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene oxide.
[0033] When the graft copolymer resin is mixed with a thermoplastic resin to prepare a thermoplastic resin composition, the content of the graft copolymer resin is not particularly limited and can be appropriately adjusted in consideration of the types of the graft copolymer resin and the thermoplastic resin, and can be, for example, 10 to 50 mass% based on the total amount of the thermoplastic resin composition.
[0034] The thermoplastic resin composition can be obtained in the form of pellets by melt kneading using a known device such as a Banbury mixer, a roll mill, or a twin-screw extruder. The obtained thermoplastic resin composition can be appropriately blended with a plasticizer, a lubricant, a flame retardant, a pigment, a filler, a fiber reinforcement, etc. as necessary. The thermoplastic resin composition thus obtained can be molded by injection molding, extrusion molding, compression molding, injection compression molding, blow molding, etc. EXAMPLES
[0035] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Note that percentages shown in the examples are based on mass.
[0036] [Production of crosslinked butyl acrylate rubber latex (a-1)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixed solution of 85 parts by weight of butyl acrylate and 0.60 parts by weight of allyl methacrylate and an emulsifier aqueous solution of 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-1).
[0037] [Production of crosslinked butyl acrylate rubber latex (a-2)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.0275 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.4725 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-2).
[0038] [Production of crosslinked butyl acrylate rubber latex (a-3)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.022 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.378 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-3).
[0039] [Production of crosslinked butyl acrylate rubber latex (a-4)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.0165 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.2835 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-4).
[0040] [Production of cross-linked butyl acrylate rubber latex (a-5)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.011 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.189 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-5).
[0041] [Production of crosslinked butyl acrylate rubber latex (a-6)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.0055 parts by weight of t-dodecyl mercaptan, 0.15 parts by weight of sodium dodecylbenzenesulfonate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 85 parts by weight of butyl acrylate, 0.60 parts by weight of allyl methacrylate, and 0.0945 parts by weight of t-dodecyl mercaptan, and an emulsifier aqueous solution in which 0.75 parts by weight (solid content equivalent) of sodium dodecylbenzenesulfonate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was held for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-6).
[0042] [Production of cross-linked butyl acrylate rubber latex (a-7)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 0.165 parts by weight of styrene, 0.11 parts by weight of acrylonitrile, 5.225 parts by weight of butyl acrylate, 0.0352 parts by weight of allyl methacrylate, 0.0198 parts by weight of ethylene glycol dimethacrylate, 0.375 parts by weight of disproportionated potassium rosinate (solid content equivalent), and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixture of 2.835 parts by weight of styrene, 1.89 parts by weight of acrylonitrile, 89.775 parts by weight of butyl acrylate, 0.6048 parts by weight of allyl methacrylate, and 0.3402 parts by weight of ethylene glycol dimethacrylate, and an emulsifier aqueous solution in which 2.125 parts by weight (solid content equivalent) of disproportionated potassium rosinate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was heated to 70°C and aged for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-7).
[0043] [Production of cross-linked butyl acrylate rubber latex (a-8)] A nitrogen-purged glass reactor was charged with 219 parts by weight of deionized water, 10 parts by weight of styrene, 5.0 parts by weight of butyl acrylate, 0.035 parts by weight of allyl methacrylate, 0.75 parts by weight (solid content equivalent) of disproportionated potassium rosinate, and 0.15 parts by weight of potassium persulfate, and the mixture was reacted at 65°C for 1 hour. Thereafter, a mixed solution of 85 parts by weight of butyl acrylate and 0.60 parts by weight of allyl methacrylate and an emulsifier aqueous solution in which 4.25 parts by weight (solid content equivalent) of disproportionated potassium rosinate was dissolved in 24 parts by weight of deionized water were continuously added over a period of 3 hours. After the dropwise addition, the mixture was maintained for 3.5 hours to obtain a crosslinked butyl acrylate rubber latex (a-8).
[0044] <Gel content measurement method> The gel content of each of the crosslinked butyl acrylate rubber latexes (a-1) to (a-8) was measured by the following method. After drying the above-mentioned crosslinked butyl acrylate rubber latex, 0.25 g was immersed in 100 ml of toluene for 48 hours, filtered through a 300 mesh wire net, and the filtration residue was completely dried. The weight (W0) before and after immersion in toluene and the weight (W1) of the completely dried filtration residue were measured, and the gel content was calculated from the following formula. The results are shown in Table 1. (W1 / W0) x 100 = gel content [%]
[0045] [Table 1]
[0046] [Production of Graft Copolymer Resin (A-1)] Into a nitrogen-purged glass reactor, 50 parts by weight (solid content equivalent) of crosslinked butyl acrylate rubber latex (a-1) was charged and nitrogen-purged. After nitrogen-purging, the temperature inside the tank was raised to 60°C, and an aqueous solution of 0.40 parts by weight of glucose, 0.025 parts by weight of anhydrous sodium pyrophosphate, and 0.001 parts by weight of ferrous sulfate dissolved in 9.0 parts by weight of deionized water was added. After reaching 65°C, a mixture of 13 parts by weight of acrylonitrile (ACN), 37 parts by weight of styrene (STY), and 0.1 parts by weight of t-dodecyl mercaptan (TDM) and an aqueous emulsifier solution of 1.0 parts by weight of potassium oleate and 0.28 parts by weight of t-butyl hydroperoxide (solid content equivalent) dissolved in 16 parts by weight of deionized water were continuously dropped over 6 hours. After dropping, the mixture was held for 2 hours to obtain graft copolymer resin (A-1).
[0047] [Production of Graft Copolymer Resin (A-2)] Graft copolymer resin (A-2) was produced in the same manner as in the production of graft copolymer resin (A-1), except that a mixed liquid containing acrylonitrile, styrene, butyl acrylate (BA) and t-dodecyl mercaptan was used as the mixed liquid and the amount added was changed to the amount (unit: parts by weight) shown in Table 2.
[0048] [Production of Graft Copolymer Resins (A-3) to (A-6)] Graft copolymer resins (A-3) to (A-6) were produced in the same manner as in the production of the graft copolymer resin (A-1), except that the crosslinked butyl acrylate rubber latexes (a-2) to (a-5) were used instead of the crosslinked butyl acrylate rubber latex (a-1).
[0049] [Production of Graft Copolymer Resin (A-7)] Graft copolymer resin (A-7) was produced in the same manner as in the production of graft copolymer resin (A-2), except that crosslinked butyl acrylate rubber latex (a-5) was used instead of crosslinked butyl acrylate rubber latex (a-1).
[0050] [Production of Graft Copolymer Resin (A-8)] Graft copolymer resin (A-8) was produced in the same manner as in the production of graft copolymer resin (A-1), except that crosslinked butyl acrylate rubber latex (a-6) was used instead of crosslinked butyl acrylate rubber latex (a-1).
[0051] [Production of Graft Copolymer Resin (A-9)] Into a nitrogen-purged glass reactor, 50 parts by weight (solid content equivalent) of crosslinked butyl acrylate rubber latex (a-7) was charged and nitrogen-purged. After nitrogen-purging, the temperature in the tank was raised to 65°C, and an aqueous solution of 0.40 parts by weight of lactose, 0.025 parts by weight of anhydrous sodium pyrophosphate, and 0.001 parts by weight of ferrous sulfate dissolved in 9.0 parts by weight of deionized water was added. After reaching 70°C, a mixture of 12.5 parts by weight of acrylonitrile and 37.5 parts by weight of styrene and an emulsifier aqueous solution of 1.0 parts by weight of disproportionated potassium rosinate and 0.28 parts by weight of t-butyl hydroperoxide (solid content equivalent) dissolved in 16 parts by weight of deionized water were continuously dropped over 6 hours. After dropping, the mixture was held for 2 hours to obtain a graft copolymer resin (A-9).
[0052] [Production of Graft Copolymer Resin (A-10)] Graft copolymer resin (A-10) was produced in the same manner as in the production of graft copolymer resin (A-1), except that crosslinked butyl acrylate rubber latex (a-8) was used instead of crosslinked butyl acrylate rubber latex (a-1).
[0053] [Production of Graft Copolymer Resin Powder (B-1)] Deionized water was charged into a single-tank coagulation tank equipped with an agitator blade so that the slurry concentration would be 18% when 100 parts by weight of graft copolymer resin (solid content equivalent) was added to the tank. Then, 4.0 parts by weight of magnesium sulfate was added and the temperature was raised to 85°C. After reaching 85°C, 100 parts by weight of graft copolymer resin (A-1) and 1.3 parts by weight of disproportionated potassium rosinate were added. After the addition, the temperature was raised to 95°C and held for 1 minute, followed by washing with water, dehydration, and drying in a hot air dryer at 90°C for 14 hours to obtain graft copolymer resin powder (B-1).
[0054] [Production of Graft Copolymer Resin Powders (B-2) to (B-10)] Graft copolymer resin powders (B-2) to (B-10) were produced in the same manner as in the production of the graft copolymer resin (B-1) above, except that graft copolymer resins (A-2) to (A-10) were used instead of graft copolymer resin (A-1).
[0055] <Measurement of swelling degree of graft copolymer contained in graft copolymer resin> For the graft copolymer resin powders (B-1) to (B-10), the swelling degree of the graft copolymer contained in the graft copolymer resin was measured. Specifically, 4.0 g of the graft copolymer resin powder was weighed out, 50 mL of acetone was added, and the mixture was left for 16 hours. After that, the insoluble matter was separated from the soluble matter by centrifugation (20,000 rpm for 1 hour). The separated insoluble matter was vacuum-dried at room temperature for one day to prepare a measurement sample. The insoluble matter corresponds to the graft copolymer. 1 g of the sample was immersed in 50 ml of a methyl ethyl ketone / toluene solution (weight ratio 1 / 1) for 16 hours, and the weight A of the precipitate was measured after centrifugation (12,000 rpm·40 min). The precipitate was allowed to stand in a draft for 2 hours and then dried at 80° C. for 3 hours, after which the weight B of the resulting dried product was measured. The swelling degree of the graft copolymer was calculated based on the following formula. Swelling index (SI) = (weight of precipitate A) / (weight of dry matter B)
[0056] [Table 2]
[0057] [Production of Copolymer (C-1)] A copolymer (C-1) consisting of 74.5 parts by weight of styrene and 25.5 parts by weight of acrylonitrile was obtained by a known bulk polymerization method. The reduced viscosity of the obtained copolymer (C-1) was measured by the following method, and the reduced viscosity was 0.62 dl / g. Dissolve in N,N-dimethylformamide to give a solution with a concentration of 0.4 g / 100 ml, and then measure the flow time at 30°C using a Cannon-Fenske viscometer to determine the reduced viscosity.
[0058] (Solvent resistance evaluation of graft copolymer resin powder) The graft copolymer resin powders (B-1) to (B-10) and copolymer (C-1) were mixed in the amounts shown in Table 3, and then melt-kneaded at 240°C using a 40 mm twin-screw extruder and pelletized to obtain pellets of a thermoplastic resin composition. Using the obtained pellets, a test piece measuring 10 cm long x 2 cm wide x 0.2 cm thick was made using a press. For evaluation, a solvent was applied to the side where the test piece was fixed using a cantilever jig, and loads (800 g and 600 g) were applied to the other side, and the test piece was observed for 3 minutes and evaluated according to the following criteria. The results are shown in Table 3. As the solvent, hexane / ethanol = 1 / 1 (weight ratio) was used. ◎: Does not break when tested at 800g and 600g. ○: It breaks in the 800g test, but does not break in the 600g test. ×: Breaks when tested at 600g.
[0059] [Table 3]
Claims
[Claim 1] A graft copolymer resin obtained by graft polymerizing an aromatic vinyl monomer and a vinyl monomer including an alkyl (meth)acrylate ester onto a rubber-like polymer including a structural unit derived from a (meth)acrylic acid ester, the swelling degree of the graft copolymer contained in the graft copolymer resin in a mixed solvent of methyl ethyl ketone and toluene (mass ratio 1:1) is 8.0 or more; A graft copolymer resin, in which the content of the (meth)acrylic acid alkyl ester in the vinyl monomer is 5 to 30 mass % based on the total amount of the vinyl monomer.
Citation Information
Patent Citations
Process for preparing highhimpact resins
JP1977047092A
Thermoplastic resin composition
JP1995173361A
Thermoplastic resin composition
JP1996113689A
Rubbery polymer latex, rubber-reinforced vinyl polymer, and thermoplastic polymer composition
JP1997316138A
Thermoplastic resin molding and its production
JP1997316291A
